Enzyme-linked immunosorbent Assay for detecting of antibody to canine distemper virus - ., Sudarisman (Indonesian Animal Sciences Society, 2006)
Serum neutralisation test (SNT) has been established for evaluating canine distemper vaccination, but until now SNT was rarely used due to the need for continuous tissue culture facilities and requires 3 days to perform. For detecting antibody to canine distemper virus, an enzyme-linked immunosorbent assay (ELISA) is relatively simple and rapid seroassay. ELISA for canine immunoglobulin (Ig) G antibodies to canine distemper virus (CDV) was developed by using Onderstepoort strain of canine distemper virus as coating antigen. Rabbit anti canine IgG labelled with horse radish peroxidase was used as the conjugate, while phenylenediamine dihydrochloride (OPD) was used as the substrate. The ELISA results were then compared with the results of the SNT, using the sera of 312 random-source dogs from West Java. The two test-results had a high degree of correlation. Very few discrepancies occurred and most of these were at the lower limits of each test. When the sera were tested at 1 : 100 dilutions, there was a 95.5% agreement between the ELISA and SNT. Their sensitivity and spesificity were 83.9 and 98.4%. Titrated SNT and ELISA also were performed on sera from 7 dogs whose lifetime medical histories were known. The antibodies were inclining up after two months of post vaccination, where the titre was not in zero/lower position at the day of vaccination. However, antibody zero or low position were found at 28 days post vaccination. All of the results indicated that ELISA can be used for evaluating antibody to canine distemper virus response, replacing the SNT. Key Words: ELISA, Serum Neutralization Test, Distemper, Dogs